Overview of Increased Lactic Acid and Work Fatigue in Harvesting Workers at PT. X Kampar Regency - Wahyu Ramadhan; Yuharika Pratiwi; Dinda Queenty Dzakiyah Hartono (Lembaga Pengembangan Kinerja Dosen, 2025)
Work fatigue is a physical condition that weakens workers, causing less than optimal work capacity and endurance. Lactic acid is produced from anaerobic metabolism or carbohydrate metabolism without oxygen. This happens because there is not enough oxygen to support muscle energy production. The body that cannot produce the amount of lactic acid that is comparable to the rate of its synthesis, then the muscle pH will decrease, this is what inhibits glycolysis enzymes resulting in physical fatigue. Physical fatigue is the effect of increased levels of lactic acid in the body, especially muscles. One of the jobs at PT. X in Kampar Regency that can cause work fatigue is a palm oil harvester. This study is an observational study type with a cross-sectional study design. Data were obtained using interviews using a BMI questionnaire. Data collection was also carried out to obtain BMI measurement data, pulse measurements, blood pressure measurements, and lactic acid measurements with Accutrend Plus Roche Brand on 138 harvesters at PT. X Kampar Regency. In this study, the independent variable is the level of lactic acid and the dependent variable is work fatigue. The results of the study showed that the harvesters who experienced moderate work fatigue were 13 people (11.4%). The harvesters who experienced high work fatigue were 54 people (47.4%). The harvesters who experienced very high work fatigue were 47 people (41.2%). The high proportion of workers who experienced high and very high work fatigue (88.6%) reflects the significant physical workload that must be faced by oil palm harvesters at PT. X. Harvesters with lactic acid levels <2 mmol/l (not increasing) were 13 people (11.4%) and harvesters with lactic acid levels> 2 mmol/l (increasing/hyperlactatemia) were 101 people (88.6%). From the results obtained, a significant increase in lactic acid levels in 88.6% of respondents indicated that most workers experienced higher muscle fatigue conditions during work with increased lactic acid levels.